Quantitative study of the impact of land use change on groundwater level in the Songnen Plain, China - Zhong Lu; Jinliang Zhang; Dengming Yan; Chaoqun Li; Guoping Lei; Zhiqiang Dong; Quanlai Ma (Journal of Hydrology: Regional Studies)
Study region: the Songnen Plain, China Study focus: Groundwater, being a significant constituent of terrestrial water supplies, has consistently garnered considerable attention. In recent years, there have been significant oscillations in groundwater levels, mostly attributed to changes in the underlying surface. Nonetheless, there is a scarcity of investigations that effectively assess the influence of alterations in land use on the levels of groundwater. In this study, the MIKE SHE/MIKE 11 model is employed to simulate the process of groundwater level change in the Songnen Plain over a span of four decades. Scenario analysis is utilized to investigate the influence of climate change and human activities on groundwater level change. Additionally, the impact of various land use changes on groundwater level change is quantified using the center of gravity offset model. New hydrological insights for the region: The study showcased the great simulation accuracy of the MIKE SHE/MIKE 11 model in simulating the groundwater level on the Songnen Plain. The correlation coefficient (R) between different stations exceeds 0.8, and the Nash efficiency coefficient (NSE) surpasses 0.75. Overall, climate change is the predominant factor responsible for changes in groundwater levels, constituting around 70–80 percent of the total impact. Nevertheless, the extent of its impact on groundwater levels is growing as human activities escalate. In areas with significant human activity, the main cause of changes in groundwater levels is linked to human activities, which account for around 65–75 percent of the observed variations. Regarding the influence of various land-use types on groundwater levels, the primary factors contributing to the decrease in groundwater levels are paddy fields and construction land. Construction land has a greater impact than paddy fields. The research develops a scenario simulation technique utilizing a coupled surface-groundwater model and a center of gravity offset model, enabling a quantitative analysis of the effects of various land use changes on groundwater levels across different scales. This methodology aids in decision-making to enhance groundwater resource efficiency and optimize water resource management.